STORES ATMOSPHERE AND PROMOTION ON CUSTOMER SATISFACTION AND ITS IMPACT ON CONSUMER LOYALTY - Suryana, Popo; Haryadi, Mochammad Rifal (TRIKONOMIKA, 2019)
Le Delice Cafe and Bakery is a business that engaged in the culinary business. Analysis of data used is using path analysis (path analysis), multiple correlation, and coefficients of determination. Based on the analysis of the effect of the store atmosphere and promotion to customer satisfaction simultaneously is equal 159.147. While partially in the structure of I store atmosphere into a variable that has a dominant influence on customer satisfaction, because based on the calculation of standardized coefficients beta has the highest value of 0.519 compared to the promotion. While in structure II promotion become variable which have dominant influence to consumer loyalty, because based on calculation of standardized coefficients beta have highest value that is equal to 0.509 compare to store atmosphere and consumer satisfaction.